Automatic Generation of Programming Exercises - Sovietov, Peter (arXiv.org, 2022)
Massive training of developers following the growing demands of the information technology industry requires teachers to automate their repetitive tasks. For training courses on programming, it is promising to use automatic generation and automatic grading of exercises that require a student to write a program. This article discusses the general scheme for constructing a programming exercises generator and identifies two classes of exercises, the generation of which can be automated: converting notation into code and converting data formats. Several examples of programming exercise generators are discussed. The experience of using exercise generators for the Python programming course is briefly described.